Wavelength conversion component and light emitting device

By using glass matrix and phosphor layer structures with different transmittance in the light-emitting device, the problems of low phosphor excitation efficiency and leakage under ultraviolet light excitation are solved, achieving high-efficiency fluorescence emission and device protection, and simplifying the manufacturing process.

CN117120886BActive Publication Date: 2026-11-06NIPPON ELECTRIC GLASS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202280026544.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-04-01
Filing Date
2022-03-18
Publication Date
2026-11-06
Estimated Expiration
2042-03-18

AI Technical Summary

Technical Problem

When using ultraviolet light as excitation light, existing light-emitting devices suffer from low excitation efficiency of phosphors and ultraviolet leakage, which leads to aging of surrounding equipment and adverse effects on human health, and increases the complexity of the manufacturing process.

Method used

The wavelength conversion component is formed by using a first layer composed of a first glass matrix and phosphor particles, and a second layer composed of a second glass matrix to ensure that the absolute value of the difference in transmittance between the excitation wavelength light and the fluorescence wavelength light is greater than a certain value, and that the transmittance of the second layer is lower than that of the first layer and the thickness of the second layer is greater than that of the first layer, so as to shield ultraviolet leakage.

Benefits of technology

It achieves efficient excitation of phosphors under ultraviolet light, suppresses equipment aging and human health effects caused by ultraviolet leakage, simplifies the manufacturing process, and improves the luminescence efficiency and reliability of the device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117120886B_ABST
    Figure CN117120886B_ABST
Patent Text Reader

Abstract

The wavelength conversion member 1 is a member for converting the wavelength of excitation light emitted from a light source 7, and includes a first layer 2 composed of a first glass matrix 4 and phosphor particles 5 dispersed in the first glass matrix 4; and a second layer 3 disposed on the first layer 2 and composed of a second glass matrix 6, the first layer 2 being disposed on the light source 7 side, the transmittance T of the first glass matrix 4 for light of the excitation wavelength A is greater than the transmittance L of the second glass matrix 6 for light of the excitation wavelength B . The difference (|T A -T B |) between the transmittance T of the first glass matrix 4 for light of the excitation wavelength and the transmittance T A of the second glass matrix 6 for light of the excitation wavelength is greater than the difference (|L B -L A |) between the transmittance L of the first glass matrix 4 for light of the fluorescent wavelength and the transmittance L B of the second glass matrix 6 for light of the fluorescent wavelength, and T A >T B .
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a wavelength conversion component that converts the wavelength of light emitted by a light-emitting diode (LED) or laser diode (LD) into another wavelength, and to a light-emitting device using the wavelength conversion component. Background Technology

[0002] In recent years, as a next-generation light-emitting device to replace fluorescent lamps and incandescent lamps, LED and LD light-emitting devices have received increasing attention due to their advantages such as low power consumption, small size, light weight, and ease of light intensity adjustment. As an example of such a device, Patent Document 1 discloses a light-emitting device in which a wavelength conversion component is disposed on an LED emitting blue light to absorb part of the light from the LED and convert it into yellow light. This device emits white light, which is a composite of blue light emitted from the LED and yellow light emitted from the wavelength conversion component.

[0003] As a light-emitting device using LEDs and LDs, a light-emitting device for sensing applications has also been proposed, not only for general lighting purposes but also for wavelength conversion components and sensor combinations. For example, Patent Document 2 below discloses a light source for a methane gas sensor comprising a light-emitting element that emits ultraviolet light and / or visible light and a phosphor layer disposed on the light-emitting element.

[0004] Existing technical documents

[0005] Patent documents

[0006] Patent Document 1: Japanese Patent Application Publication No. 2000-208815

[0007] Patent Document 2: Japanese Patent Application Publication No. 2013-170205 Summary of the Invention

[0008] The problem that the invention aims to solve

[0009] When excitation light leaks to the outside along with fluorescence, it may adversely affect the sensor's function. Furthermore, ultraviolet light with shorter wavelengths can also have adverse effects on the human body. Therefore, in the light-emitting device described in Patent Document 2, a filter structure is formed on the surface of the phosphor layer that prevents excitation light from passing through, allowing only fluorescence to pass through. However, forming such a filter structure on the phosphor layer surface leads to a problem of increased manufacturing complexity and higher costs.

[0010] In view of the above, the object of the present invention is to provide a wavelength conversion component that can efficiently excite phosphors even when ultraviolet light is used as excitation light, and can suppress the aging of peripheral equipment and the effects on the human body caused by ultraviolet leakage, and a light-emitting device using the wavelength conversion component.

[0011] Technical solutions for solving the problem

[0012] The wavelength conversion component of the present invention is characterized in that, for converting the wavelength of excitation light emitted from a light source, it comprises a first layer consisting of a first glass matrix and phosphor particles dispersed in the first glass matrix; and a second layer disposed on the first layer and consisting of a second glass matrix, wherein the first layer is disposed on the light source side, and the transmittance T of the excitation wavelength light through the first glass matrix is ​​T. A The transmittance T of the second glass matrix mentioned above B The difference | T A -T B The transmittance L of light with wavelengths greater than fluorescence through the first glass matrix described above A The transmittance L of the second glass matrix mentioned above B The difference | L A -L B |, and T A >T B .

[0013] In this invention, the difference |T| between the light transmittance difference of the excitation wavelength and the light transmittance difference of the fluorescence wavelength is... A -T B |-|L A -L B | Preferably 20% or more.

[0014] In this invention, the preferred transmittance T of the first glass matrix to the excitation wavelength is... A The transmittance T of the second glass matrix to the excitation wavelength is above 20%. B It is below 65%.

[0015] In this invention, the transmittance L of the first glass matrix to fluorescence wavelength is preferably [value missing]. A The transmittance L of the second glass matrix to fluorescence wavelengths is above 50%. B It is over 50%.

[0016] In this invention, it is preferable that the second layer described above is substantially free of fluorescent particles.

[0017] In this invention, it is preferable that the thickness of the second layer is greater than the thickness of the first layer.

[0018] In this invention, it is preferable that the thickness ratio of the second layer to the first layer (second layer / first layer) is 1 or more and 30 or less.

[0019] In this invention, the excitation light is preferably UV light.

[0020] In this invention, the fluorescence is preferably visible light.

[0021] The light-emitting device of the present invention is characterized by comprising a light source that emits excitation light and a wavelength conversion component formed in accordance with the present invention.

[0022] Invention Effects

[0023] According to the present invention, a wavelength conversion component can be provided that can efficiently excite phosphors even when UV light (ultraviolet light) is used as excitation light, and can suppress the aging of peripheral equipment and the effects on the human body caused by UV light leakage without the need for an external filter, as well as a light-emitting device using the wavelength conversion component. Attached Figure Description

[0024] Figure 1 This is a front cross-sectional view of a wavelength conversion component according to one embodiment of the present invention.

[0025] Figure 2 This is a schematic diagram of an example of the transmittance spectrum of the first and second glass matrices.

[0026] Figure 3 This is a front cross-sectional view of a light-emitting device according to one embodiment of the present invention.

[0027] Figure 4 This is a front cross-sectional view of a modified example of a light-emitting device according to one embodiment of the present invention.

[0028] Figure 5 This is a schematic diagram of an example of the energy distribution spectrum of light emitted from the emission surface of a wavelength conversion component after being irradiated by a UV LED. Detailed Implementation

[0029] Preferred embodiments are described below. However, these embodiments are merely illustrative, and the present invention is not limited to them. Furthermore, in the various figures, components having substantially the same function are sometimes labeled with the same symbol.

[0030] Wavelength conversion component

[0031] Figure 1 This is a front cross-sectional view of a wavelength conversion component according to one embodiment of the present invention. Figure 1As shown, the wavelength conversion component 1 of this embodiment has a rectangular plate shape. Of course, the wavelength conversion component 1 may also have a generally circular plate shape, and its shape is not particularly limited.

[0032] The wavelength conversion component 1 includes a first layer 2 and a second layer 3. The first layer 2 has a first main surface 2a and a second main surface 2b. The second layer 3 is disposed on the first main surface 2a of the first layer 2. In addition, the second main surface 2b of the first layer 2 is the surface on the side where the light source 7 is disposed. Therefore, the second layer 3 is disposed on the side opposite to the side of the light source 7.

[0033] The first layer 2 is a phosphor glass composed of a first glass matrix 4 and phosphor particles 5. In this embodiment, the phosphor particles 5 are dispersed in the first glass matrix 4. The second layer 3 is composed of a second glass matrix 6.

[0034] In this embodiment, such as Figure 1 As shown, excitation light A from light source 7 is emitted into wavelength conversion component 1. Excitation light A enters the first layer 2 from the second main surface 2b side. When excitation light A irradiates the first layer 2 where phosphors are disposed, fluorescence B is emitted. Fluorescence B passes through the second layer 3 and is emitted from wavelength conversion component 1.

[0035] Figure 2 This is a schematic diagram illustrating an example of the transmittance spectrum of the first glass matrix 4 and the second glass matrix 6 constituting the wavelength conversion component 1. It should be noted that... Figure 2 The transmittance spectra of the first glass matrix 4 and the second glass matrix 6 are shown separately. The transmittance spectra of the first glass matrix 4 and the second glass matrix 6 are the results of measurements taken on glass plates with a thickness of 1 mm. This glass plate can be prepared by pressing glass powder (average particle size 2.5 μm) used as raw materials for the first glass matrix 4 and the second glass matrix 6 into a powder body, vacuum-sintering it at a temperature of glass powder softening temperature +50°C to obtain a sintered body, and then subjecting the resulting sintered body to cutting, grinding, and polishing processes to achieve a thickness of 1 mm. The transmittance shown in this invention refers to the total light transmittance of the sintered body with a thickness of 1 mm after polishing and grinding, and can be measured according to the method in JIS K7105. Furthermore, the transmittance spectra of the first glass matrix 4 and the second glass matrix 6 can be measured using a spectrophotometer.

[0036] like Figure 2 As shown, in this embodiment, the transmittance T of the light at the excitation wavelength through the first glass matrix 4 is... A Transmittance T of the second glass matrix 6 B The absolute value of the difference |T A -T B The transmittance L of light with wavelengths greater than fluorescence wavelength to the first glass matrix 4 is... ATransmittance L of the second glass matrix 6 B The difference | L A -L B More specifically, at the excitation wavelength, the transmittance T of the first glass matrix 4... A The transmittance T is greater than that of the second glass matrix 6. B On the other hand, at the fluorescence wavelength, the transmittance L of the first glass matrix 4 is... A The transmittance L of the second glass matrix 6 B Both are large, but the difference between them is small. In this invention, the excitation wavelength refers to the wavelength that maximizes the luminous intensity of the laser source, and the fluorescence wavelength refers to the wavelength that maximizes the fluorescence intensity. It should be noted that, in this embodiment, the transmittance of the excitation wavelength refers to UV light, specifically the transmittance of light with wavelengths of 200nm to 380nm. The transmittance of the fluorescence wavelength refers to visible light, specifically the transmittance of light with wavelengths of 380nm to 800nm.

[0037] When UV light is incident as excitation light A into the wavelength conversion component 1, which uses a first glass matrix 4 and a second glass matrix 6 having such optical properties, the first glass matrix 4 constituting the first layer 2 has high transmittance for excitation wavelength light. Therefore, absorption of excitation light A by the glass is reduced, and the wavelength can be efficiently converted into fluorescence in the first layer 2. On the other hand, in the second layer 3, since the second glass matrix 6 constituting the second layer 3 has low transmittance for excitation wavelength light, UV light used as excitation light A can be shielded in the second layer 3. Therefore, aging of peripheral equipment and effects on the human body caused by UV light leakage can be suppressed. In addition, since the first glass matrix 4 and the second glass matrix 6 constituting the first layer 2 and the second layer 3 have high transmittance for fluorescence wavelength light, fluorescence can be emitted efficiently. Therefore, the wavelength conversion component 1 according to this embodiment can efficiently excite phosphors even when UV light is used as excitation light A, and can suppress aging of peripheral equipment and effects on the human body caused by UV light leakage.

[0038] In this invention, the transmittance difference for light of the excitation wavelength and the transmittance difference for light of the fluorescence wavelength |T A -T B |-|L A -L B | Preferably 20% or more, more preferably 40% or more, further preferably 60% or more, and particularly preferably 75% or more. When the above difference |T A -T B |-|L A -L BAbove the aforementioned lower limit, not only can phosphors be excited more efficiently, but UV light leakage can also be further suppressed, leading to aging of peripheral equipment and its effects on the human body. It should be noted that the aforementioned difference |T A -T B |-|L A -L B There is no upper limit to the value of |, but it can be 95%.

[0039] In this invention, the thickness of the second layer 3 is preferably greater than the thickness of the first layer 2. In this case, UV light can be shielded more reliably, and the fluorescence emission efficiency can be further improved.

[0040] In particular, the thickness ratio of the second layer 3 to the first layer 2 (second layer 3 / first layer 2) is preferably 1 or more, more preferably 1.5 or more, even more preferably 2 or more, preferably 30 or less, more preferably 10 or less, and even more preferably 7 or less. When the thickness ratio (second layer 3 / first layer 2) is above the lower limit, UV light can be shielded more reliably, and the fluorescence emission efficiency can be further improved. On the other hand, when the thickness ratio (second layer 3 / first layer 2) is below the upper limit, the luminous intensity of the wavelength conversion component can be further improved.

[0041] It should be noted that the overall thickness of the wavelength conversion component 1 is preferably 0.1 mm or more, more preferably 0.125 mm or more, further preferably 0.15 mm or more, particularly preferably 0.175 mm or more, and most preferably 0.2 mm or more. The overall thickness of the wavelength conversion component 1 is preferably 1.5 mm or less, more preferably 1 mm or less, further preferably 0.75 mm or less, particularly preferably 0.5 mm or less, and most preferably 0.3 mm or less. When the overall thickness of the wavelength conversion component 1 is above the above-mentioned lower limit, the luminous intensity and mechanical strength of the wavelength conversion component 1 can be further improved. In addition, when the thickness of the wavelength conversion component 1 is below the above-mentioned upper limit, light scattering and absorption in the wavelength conversion component 1 can be further suppressed, and the emission efficiency of fluorescence can be further improved.

[0042] Furthermore, as described later, since the first glass matrix 4 and the second glass matrix 6 are essentially prepared by stacking green sheets as raw materials for each layer and firing them simultaneously, it is preferable that the difference in softening points between the glass powder used in the first glass matrix 4 and the glass powder used in the second glass matrix 6 is small. The difference in softening points between the glass powder used in the first glass matrix 4 and the glass powder used in the second glass matrix 6 is preferably 200°C or less, more preferably 100°C or less, further preferably 50°C or less, particularly preferably 10°C or less, and most preferably the softening points of both are the same.

[0043] (First layer)

[0044] The first layer 2 consists of a first glass matrix 4 and phosphor particles 5 dispersed in the first glass matrix 4.

[0045] First glass matrix:

[0046] The first glass matrix 4 is made of glass that can be used as a dispersion medium for phosphor particles 5 such as inorganic phosphors. Furthermore, the first glass matrix 4 is made of glass that transmits UV light and fluorescence (UV light transmitting glass).

[0047] The transmittance T of the first glass matrix 4 to the excitation wavelength A Preferably, it is 20% or more, more preferably 40% or more, further preferably 60% or more, and particularly preferably 80% or more. When the transmittance T of the first glass matrix 4 to the excitation wavelength... A Above the aforementioned lower limit, the absorption of excitation light by the glass can be further reduced, enabling the first layer 2 to emit fluorescence more efficiently. The transmittance T of the first glass matrix 4 to the excitation wavelength... A There is no upper limit, but it can be, for example, 95%.

[0048] The transmittance L of the first glass matrix 4 to fluorescence wavelengths A Preferably, it is 50% or more, more preferably 75% or more, and even more preferably 80% or more. When the transmittance L of the first glass matrix 4 to light of the fluorescence wavelength... A Above the aforementioned lower limit, the first layer 2 can emit fluorescence more efficiently. The transmittance L of the first glass matrix 4 for fluorescence wavelengths... A There is no upper limit, but it can be, for example, 95%.

[0049] There are no particular limitations on the glass constituting the first glass matrix 4, as long as it has the aforementioned optical properties. For example, borosilicate glass, phosphate glass, tin phosphate glass, bismuthate glass, and tellurate glass can be used.

[0050] As a specific example of the glass constituting the first glass matrix 4, a glass containing, for example, 40%–60% SiO2, 0.1%–35% B2O3, 0.1%–10% Al2O3, 0%–10% Li2O, 0%–10% Na2O, 0%–10% K2O, 0.1%–10% Li2O+Na2O+K2O, 0%–45% MgO, 0%–45% CaO, 0%–45% SrO, 0%–45% BaO, 0.1%–45% MgO+CaO+SrO+BaO, and 0%–15% ZnO can be used.

[0051] The glass constituting the first glass matrix 4 can also be a glass containing, by mass %, 55%–75% SiO2, 1%–10% Al2O3, 10%–30% B2O3, 0%–5% CaO, 0%–5% BaO, and 1%–15% Li2O+Na2O+K2O.

[0052] Alternatively, the glass constituting the first glass matrix 4 may also be a glass containing, by mass %, 60%–90% SiO2+B2O3, 0%–20% Li2O+Na2O+K2O, and 0%–20% MgO+CaO+SrO+BaO.

[0053] When the glass constituting the first glass matrix 4 contains Fe2O3 or TiO2, the transmittance of UV light may decrease. Therefore, it is preferable that the content of these two substances is low, and more preferably substantially absent. In this invention, "substantially absent" means that the raw materials are not intentionally present, and objectively refers to less than 1000 ppm.

[0054] It should be noted that in this specification, "x+y+..." refers to the total amount of each component.

[0055] The softening point of the first glass matrix 4 is preferably 250°C to 1000°C, more preferably 300°C to 950°C, and even more preferably 500°C to 900°C. When the softening point of the first glass matrix 4 is too low, the mechanical strength and chemical durability of the wavelength conversion component 1 may decrease; and because the first glass matrix 4 itself has low heat resistance, there is a risk of softening and deformation due to the heat generated by the phosphor particles 5. On the other hand, when the softening point of the first glass matrix 4 is too high, there is a risk that the phosphor particles 5 may age and the luminous intensity of the wavelength conversion component 1 may decrease when the manufacturing process includes a firing step. It should be noted that, from the perspective of further improving the chemical stability and mechanical strength of the wavelength conversion component 1, the softening point of the first glass matrix 4 is preferably 500°C or higher, more preferably 600°C or higher, and even more preferably 650°C or higher. However, when the softening point of the first glass matrix 4 increases, the firing temperature also increases, resulting in a risk of increased manufacturing costs. Furthermore, when the heat resistance of the phosphor particles 5 is low, there is a risk of aging due to firing. Therefore, in order to manufacture the wavelength conversion component 1 at a lower cost or to reduce the heat resistance of the phosphor particles 5, the softening point of the first glass matrix 4 is preferably 550°C or less, more preferably 530°C or less, even more preferably 500°C or less, particularly preferably 480°C or less, and most preferably 460°C or less.

[0056] Fluorescent particles:

[0057] There are no particular limitations on the phosphor particle 5, as long as it can emit fluorescence when excitation light is incident on it. Examples of phosphor particles 5 include oxide phosphors, nitride phosphors, oxynitride phosphors, chloride phosphors, oxychloride phosphors, sulfide phosphors, oxysulfide phosphors, halide phosphors, chalcogenide phosphors, aluminate phosphors, halophosphate phosphors, or garnet-based compound phosphors. These phosphors can be used individually or in combination. Examples of phosphors that absorb UV light and emit visible light include Lu3Al5O3. 12 (fluorescence wavelength 550nm), Si 6-z Al z O z N 8-z Eu (0 < z < 4.2) (i.e., β-SiAlON:Eu) (fluorescence wavelength 545nm), La3Si6N 11 Ce (fluorescence wavelength 535nm), etc.

[0058] The average particle size of the phosphor particles 5 is preferably 1 μm or more, and more preferably 5 μm or more. When the average particle size of the phosphor particles 5 is too small, it may result in poor quantum efficiency and reduced luminescence intensity. On the other hand, when the average particle size of the phosphor particles 5 is too large, it may result in poor dispersion in the first glass matrix 4 and uneven luminescence color. Therefore, the average particle size of the phosphor particles 5 is preferably 50 μm or less, and more preferably 25 μm or less.

[0059] It should be noted that, in this specification, the average particle size refers to the average particle size D measured by a laser diffraction measuring device. 50 .

[0060] The content of phosphor particles 5 in the first layer 2 is preferably 1% by volume or more, more preferably 3% by volume or more, and even more preferably 5% by volume or more. The content of phosphor particles 5 in the first layer 2 is preferably 70% by volume or less, more preferably 65% ​​by volume or less, and even more preferably 50% by volume or less. When the content of phosphor particles 5 is too low, the thickness of the first layer 2 needs to be increased to achieve the required fluorescence intensity. As a result, the light extraction efficiency may decrease due to increased internal scattering of the wavelength conversion component 1 and absorption caused by the matrix. On the other hand, when the content of phosphor particles 5 is too high, the proportion of glass is relatively reduced, the supporting force of the glass on the phosphor is weakened, and the mechanical strength of the wavelength conversion component 1 may decrease.

[0061] In this embodiment, the second glass matrix 6 is made of a powder sintered body containing only glass powder, but it is not limited to this. The second glass matrix 6 may also contain other inorganic powders such as filler powder for purposes such as adjusting the coefficient of thermal expansion and light scattering effect. In this way, it is easy to match the coefficients of thermal expansion of the first layer 2 and the second layer 3, and further suppress warping, cracking, etc. of the wavelength conversion component 1 caused by the difference in coefficients of thermal expansion. In addition, the light scattering effect of the filler powder can further improve the luminous intensity of the wavelength conversion component 1. Moreover, since it contains filler powder with high thermal conductivity, the heat dissipation efficiency of the wavelength conversion component 1 can be further improved. Examples of filler powders include MgO, Al2O3, BN, and AlN. Among them, MgO, Al2O3, and BN are preferred because of their good transmittance in the visible light range.

[0062] First layer:

[0063] The thickness of the first layer 2 is not particularly limited, but is preferably 0.01 mm or more, more preferably 0.03 mm or more, preferably 0.5 mm or less, more preferably 0.3 mm or less. When the thickness of the first layer 2 is above the aforementioned lower limit, the luminous intensity and mechanical strength of the wavelength conversion component 1 can be further improved; while when the thickness of the first layer 2 is below the aforementioned upper limit, light scattering and absorption in the first layer 2 can be further suppressed, and the fluorescence emission efficiency can be further improved.

[0064] Second layer:

[0065] The second layer 3 is composed of a second glass matrix 6. The second glass matrix 6 is composed of glass (such as UV light shielding glass) that shields excitation light (e.g., UV light) while allowing fluorescence to pass through.

[0066] The transmittance T of the second glass matrix 6 to the excitation wavelength B Preferably, it is 65% or less, more preferably 40% or less, further preferably 20% or less, and particularly preferably 10% or less. When the transmittance T of the second glass matrix 6 to the excitation wavelength... B Below the aforementioned upper limit, the excitation light can be more reliably shielded in the second layer 3. For example, when the excitation light is UV light, the aging of peripheral equipment and its effects on the human body due to leakage can be more reliably suppressed. The transmittance T of the second glass matrix 6 to the excitation wavelength... B The lower limit is not specifically limited and can be, for example, 0%.

[0067] The transmittance L of the second glass matrix 6 to fluorescence wavelengths B Preferably, it is 50% or more, more preferably 75% or more, and even more preferably 80% or more. When the transmittance L of the second glass matrix 6 to light of the fluorescence wavelength... BAbove the aforementioned lower limit, fluorescence can be emitted more effectively in wavelength conversion component 1. The transmittance L of the second glass matrix 6 for fluorescence wavelengths... B There is no specific upper limit, and it can be, for example, 95%.

[0068] There are no particular limitations on the glass constituting the second glass matrix 6, as long as it has the above-mentioned optical properties, such as borosilicate glass, phosphate glass, tin phosphate glass, bismuthate glass, and tellurate glass can be used.

[0069] As a specific example of the glass constituting the second glass matrix 6, a glass containing, for example, 40%–60% SiO2, 0.1%–35% B2O3, 0.1%–10% Al2O3, 0%–10% Li2O, 0%–10% Na2O, 0%–10% K2O, 0.1%–10% Li2O+Na2O+K2O, 0%–45% MgO, 0%–45% CaO, 0%–45% SrO, 0%–45% BaO, 0.1%–45% MgO+CaO+SrO+BaO, 0%–15% ZnO, and 0.001%–10% CeO2 can be used.

[0070] The glass constituting the second glass matrix 6 can also be a glass containing, by mass %, 30%–85% SiO2, 0%–30% Al2O3, 0%–50% B2O3, 0%–10% Li2O+Na2O+K2O, and 0%–50% MgO+CaO+SrO+BaO.

[0071] The softening point of the second glass matrix 6 is preferably 250°C to 1000°C, more preferably 300°C to 950°C, and even more preferably 500°C to 900°C. When the softening point of the second glass matrix 6 is too low, the mechanical strength and chemical durability of the wavelength conversion component 1 may decrease; on the other hand, when the softening point of the second glass matrix 6 is too high, there is a risk that the phosphor particles 5 may age and the luminous intensity of the wavelength conversion component 1 may decrease when the manufacturing process includes a firing step.

[0072] Second floor

[0073] The thickness of the second layer 3 is not particularly limited, but is preferably 0.05 mm or more, more preferably 0.1 mm or more, preferably 1 mm or less, and more preferably 0.5 mm or less. When the thickness of the second layer 3 is above the aforementioned lower limit, the excitation light can be shielded more reliably in the second layer 3. For example, when the excitation light is UV light, the aging of peripheral equipment and the effects on the human body caused by the leakage of excitation light can be suppressed more reliably. Furthermore, when the thickness of the second layer 3 is below the aforementioned upper limit, light scattering and absorption in the second layer 3 can be further suppressed, and the emission efficiency of fluorescence can be further improved.

[0074] The second layer 3 is preferably substantially free of fluorescent particles. However, the second layer 3 may also contain fluorescent particles.

[0075] (Manufacturing method of wavelength conversion component)

[0076] The following is an example of a method for manufacturing a wavelength conversion component.

[0077] First, a green sheet for forming the first layer is prepared. Specifically, a slurry containing glass particles forming the first glass matrix 4 and phosphor particles 5 is prepared. This slurry typically contains an adhesive resin, a solvent, etc. Next, the prepared slurry is coated onto a support substrate, and a doctor blade positioned at a predetermined interval from the substrate is moved relative to the slurry to form the green sheet for forming the first layer. As the support substrate, a resin film such as polyethylene terephthalate can be used.

[0078] Next, a green sheet for forming a second layer is prepared. Specifically, a slurry containing glass particles that form the second glass matrix 6 is prepared, and the process is carried out in the same manner as described above to obtain a green sheet for forming a second layer.

[0079] It should be noted that the materials used to form the glass particles of the first glass matrix 4 and the second glass matrix 6 can be the same as those used for the first glass matrix 4 and the second glass matrix 6 described above. Furthermore, the average particle size of the glass particles is preferably 0.1 μm or more, more preferably 1 μm or more, and even more preferably 2 μm or more. If the average particle size of the glass particles is too small, it may lead to increased production costs and reduced operability. On the other hand, if the average particle size of the glass particles is too large, the resulting wavelength conversion component 1 may have the risk of residual bubbles in the glass matrix after firing, and reduced light extraction efficiency of the wavelength conversion component 1. Therefore, the average particle size of the glass particles is preferably 100 μm or less, more preferably 50 μm or less, even more preferably 20 μm or less, and particularly preferably 10 μm or less. In addition, the average particle size of the phosphor particles is preferably within the range described in the first layer 2 above.

[0080] Next, a laminate is obtained by laminating the first layer green sheet and the second layer green sheet using hot pressing or the like. Then, the laminate is fired at approximately the softening point of the glass particles to about 100°C above the softening point of the glass particles to obtain a wavelength conversion component 1 comprising a sintered body of the first layer 2 and the second layer 3. The firing is preferably performed under reduced pressure, and particularly preferably under vacuum. In this case, a wavelength conversion component 1 with superior density can be obtained. Furthermore, it is preferable to fire the laminate while it is sandwiched between a pair of restraining members. In this case, the flatness of the wavelength conversion component 1 (especially the flatness of the interface between the first layer 2 and the second layer 3) can be improved, making it easier to process to the desired thickness through subsequent grinding. It should be noted that, prior to firing, it is preferable to perform a binder removal treatment at a temperature below the softening point of the glass particles. In this case, the organic component residues that contribute to light absorption and scattering can be reduced in the resulting wavelength conversion component 1, further improving the luminescence intensity.

[0081] Furthermore, it is preferable to grind the first layer 2 in the resulting sintered body to the desired thickness. Specifically, it is preferable to grind the first layer 2 in the sintered body to the desired thickness to adjust the chromaticity of the wavelength conversion component 1. Alternatively, the second layer 3 in the resulting sintered body may also be ground to the desired thickness.

[0082] It should be noted that the manufacturing method of the wavelength conversion component 1 is not limited to the method described above. Alternatively, the wavelength conversion component 1 can be obtained by, for example, firing the first layer forming green sheet and the second layer forming green sheet separately, and then hot-pressing the resulting fired bodies together or by bonding them with an adhesive.

[0083] [Light-emitting device]

[0084] Figure 3 This is a front cross-sectional view of a light-emitting device according to one embodiment of the present invention. Figure 3 As shown, the light-emitting device 11 includes a wavelength conversion component 1 according to one embodiment described above and a light source 7 that emits excitation light A to the wavelength conversion component 1. In the light-emitting device 11, the light source 7 is configured to allow the excitation light A to be directly incident on the wavelength conversion component 1 from the first layer 2 side.

[0085] The wavelength conversion component 1 of the light-emitting device 11, by setting a first layer 2 and a second layer 3, can not only efficiently excite phosphors, but also suppress the aging of peripheral equipment and the effects on the human body caused by UV light leakage.

[0086] It should be noted that the configuration of light source 7 is not limited to the above-described form. For example... Figure 4In the illustrated variation, a light guide plate 12 is disposed between the light source 7 and the wavelength conversion component 1. The light source 7 is configured to allow excitation light A to directly enter 12. The excitation light A emitted from the light source 7 passes through the light guide plate 12 and enters the wavelength conversion component 1. Specifically, the excitation light A enters from the end face of the light guide plate 12, exits from the main surface of the light guide plate 12, and enters the wavelength conversion component 1. In this invention, the light guide plate 12 is made of a material capable of suppressing the absorption of excitation light A as much as possible.

[0087] The light-emitting device 11 can be appropriately used, for example, a light-emitting device for sensing and high color rendering illumination.

[0088] The present invention will now be described in further detail with reference to specific embodiments. The present invention is not limited to these embodiments in any way, and may be implemented with appropriate modifications without altering its essential points.

[0089] (Example 1)

[0090] As glass particles forming the first glass matrix, glass particles A were prepared with the following composition (mol%): SiO2 45%, Al2O3 4%, B2O3 18%, Li2O 1.5%, Na2O 1.5%, K2O 1.5%, BaO 25%, and ZnO 3.5% (softening point: 690℃, coefficient of thermal expansion: 86.1 × 10⁻⁶). ﹣7 / ℃, average particle size: 2.5μm).

[0091] Next, glass particles A and phosphor particles (Lu3Al5O) were added. 12 The following components were mixed: an average particle size of 15 μm, a binder resin (OLYCOX manufactured by Kyoeisha Chemical Co., Ltd.), a plasticizer (dioctyl adipate), a dispersant (FLOWLENG-700 manufactured by Kyoeisha Chemical Co., Ltd.), and an organic solvent (butanone), to obtain a slurry mixture. The resulting slurry mixture was then formed into sheets using a doctor blade method and dried at room temperature to obtain a green sheet for first layer formation. It should be noted that the amount of phosphor particles added was adjusted to 30% by volume in the first layer.

[0092] Next, as glass particles forming the second glass matrix, glass particles X were prepared with the following composition (mol%): SiO2 45%, Al2O3 4%, B2O3 18%, Li2O 1.5%, Na2O 1.5%, K2O 1.5%, BaO 25%, ZnO 3%, and CeO2 0.5% (softening point: 690℃, coefficient of thermal expansion: 86.1 × 10⁻⁶). ﹣7 / ℃, average particle size: 2.5μm).

[0093] Next, glass particles X, binder resin (OLYCOX manufactured by Kyoeisha Chemical Co., Ltd.), plasticizer (dioctyl adipate), dispersant (FLOWLEN G-700 manufactured by Kyoeisha Chemical Co., Ltd.), and organic solvent (butanone) are mixed to obtain a slurry mixture. The resulting slurry mixture is formed into a sheet by a doctor blade and dried at room temperature to obtain a green sheet for second layer formation.

[0094] Next, the green sheets for forming the first and second layers are cut to predetermined dimensions and then hot-pressed together. The resulting laminate is degreased in an electric furnace and then vacuum-fired in a vacuum gas-displacement furnace at 740°C (the softening point of the glass particles forming the first and second glass matrices + 50°C). The fired body is then ground surface by surface to achieve the desired layer thickness, resulting in a wavelength conversion component formed by the lamination of the first and second layers. It should be noted that the thickness of the first layer is 40 μm, and the thickness of the second layer is 160 μm.

[0095] (Example 2)

[0096] As glass particles forming the first glass matrix, glass particles B were prepared with the following composition by mass percentage: SiO2 68%, Al2O3 4%, B2O3 19%, Na2O 7%, K2O 1%, and F2 1% (softening point: 700℃, coefficient of thermal expansion: 41.9 × 10⁻⁶). ﹣7 / ℃, average particle size: 2.5μm).

[0097] In addition, as glass particles forming the second glass matrix, glass particles Y with the following composition by mass percentage (50% SiO2, 6% Al2O3, 5% B2O3, 12% CaO, 25% BaO, and 2% ZnO) were prepared (softening point: 850℃, coefficient of thermal expansion: 68.0 × 10⁻⁶). ﹣7 / ℃, average particle size: 2.5μm).

[0098] Furthermore, vacuum firing was performed at a temperature of 900°C (50°C higher for the glass particles forming the first glass matrix and the glass particles forming the second glass matrix).

[0099] The other aspects were implemented in the same manner as in Example 1, resulting in a wavelength conversion component. It should be noted that the thickness of the first layer is 40 μm, and the thickness of the second layer is 160 μm.

[0100] (Example 3)

[0101] As glass particles forming the first glass matrix, glass particles C were prepared with the following composition by mass percentage: SiO2 71%, Al2O3 6%, B2O3 13%, Na2O 7%, K2O 1%, CaO 1%, and BaO 1% (softening point: 737℃, coefficient of thermal expansion: 66.0 × 10⁻⁶). ﹣7 / ℃, average particle size: 2.5μm).

[0102] In addition, glass particles Y, the same as those in Example 2, were prepared as glass particles to form the second glass matrix.

[0103] Furthermore, vacuum firing was performed at a temperature of 900°C (50°C higher for the glass particles forming the first glass matrix and the glass particles forming the second glass matrix).

[0104] The other aspects were implemented in the same manner as in Example 1, resulting in a wavelength conversion component. It should be noted that the thickness of the first layer is 40 μm, and the thickness of the second layer is 160 μm.

[0105] It should be noted that the transmittance (UV-C transmittance) of the first and second glass substrates used in Examples 1-3 at a wavelength of 250 nm, a wavelength of 280 nm (transmittance at the excitation wavelength), a wavelength of 300 nm (UV-B transmittance), a wavelength of 350 nm (UV-A transmittance), and a wavelength of 550 nm (VIS transmittance = transmittance to the fluorescence wavelength) are shown in Table 1 below. Furthermore, the transmittance of the first and second glass substrates was measured on glass plates with a thickness of 1 mm. These glass plates were manufactured using the method described above. The transmittance of the first and second glass substrates was measured using a spectrophotometer (manufactured by Nippon Spectrophotometer Co., Ltd., product model V-670).

[0106] [Table 1]

[0107]

[0108] (Comparative Example 1)

[0109] As glass particles forming the first glass matrix, glass particles X, the same as those in the second glass matrix of Example 1, were prepared.

[0110] Next, glass particles X and phosphor particles (Lu3Al5O) were added. 12The following components were mixed: an average particle size of 15 μm, a binder resin (OLYCOX manufactured by Kyoeisha Chemical Co., Ltd.), a plasticizer (dioctyl adipate), a dispersant (FLOWLENG-700 manufactured by Kyoeisha Chemical Co., Ltd.), and an organic solvent (butanone), to obtain a slurry mixture. The resulting slurry mixture was then formed into sheets using a doctor blade method and dried at room temperature to obtain a green sheet. It should be noted that the amount of phosphor particles added was adjusted to 6% by volume in the obtained wavelength conversion component.

[0111] Next, the obtained green sheet was degreased in an electric furnace and then vacuum-fired at 740°C in a vacuum gas replacement furnace. The sintered body was then ground to achieve the desired layer thickness, resulting in a wavelength conversion component with only a first layer. It should be noted that the thickness of the wavelength conversion component was 200 μm.

[0112] (Comparative Example 2)

[0113] Glass particles A, identical to those in Example 1, were prepared as the glass particles forming the first glass matrix. Other aspects were carried out in the same manner as in Comparative Example 1, resulting in a wavelength conversion component with only a first layer. It should be noted that the thickness of the wavelength conversion component was 200 μm.

[0114] (Comparative Example 3)

[0115] As glass particles forming the first glass matrix, glass particles A, identical to the first glass matrix of Example 1, were prepared.

[0116] In addition, glass particles B, which are the same as those in the first glass matrix of Example 2, were prepared as glass particles to form the second glass matrix.

[0117] In addition, vacuum firing was carried out at a temperature of 750°C (50°C higher for the glass particles forming the first glass matrix and the glass particles forming the second glass matrix).

[0118] The other aspects were implemented in the same manner as in Example 1, resulting in a wavelength conversion component. It should be noted that the thickness of the first layer is 40 μm, and the thickness of the second layer is 160 μm.

[0119] (Comparative Example 4)

[0120] As glass particles forming the first glass matrix, glass particles X, the same as those in the second glass matrix of Example 1, were prepared.

[0121] In addition, glass particles Y, which are the same as those used in the second glass matrix of Example 2, were prepared as glass particles to form the second glass matrix.

[0122] In addition, vacuum firing was performed at a temperature of 900°C (50°C higher for the glass particles forming the first glass matrix and the glass particles forming the second glass matrix).

[0123] The other aspects were implemented in the same manner as in Example 1, resulting in a wavelength conversion component. It should be noted that the thickness of the first layer is 40 μm, and the thickness of the second layer is 160 μm.

[0124] (evaluate)

[0125] First, the energy distribution spectrum of the UV LED (λp = 280 nm) used as the excitation source was measured using an emission spectroscopy measuring device (manufactured by OCEAN PHOTONICS). The peak intensity at this point was set as I1.

[0126] Next, UV LEDs (λp = 280 nm) were irradiated onto each wavelength conversion component fabricated in Examples 1-3 and Comparative Examples 1-4, respectively, and the energy distribution spectrum of the light emitted from the emission surface of the wavelength conversion component was measured using the same emission spectrum measuring device (manufactured by OCEAN PHOTONICS). Figure 5 As shown in one example, the peak intensity of the transmitted light from the excitation source was measured as I2 and the fluorescence peak intensity as I3 from the obtained energy distribution spectrum. The measured ratios of I2 to I1 (I2 / I1) and I3 to I1 (I3 / I1) are shown in Table 2.

[0127] [Table 2]

[0128]

[0129] As shown in Table 2, the wavelength conversion components in Examples 1-3 have a relatively small ratio (I2 / I1), which is sufficient to shield UV light. In addition, the wavelength conversion components in Examples 1-3 have a relatively large ratio (I3 / I1), which is able to efficiently excite phosphors.

[0130] On the other hand, in the wavelength conversion components of Comparative Examples 1 and 4, the ratio (I3 / I1) is small, which cannot effectively excite the phosphor. In contrast, in the wavelength conversion components of Comparative Examples 2 and 3, the ratio (I2 / I1) is large, which cannot adequately shield UV light.

[0131] Based on the above, it can be confirmed that the difference in transmittance between the first and second glass matrices for light of the excitation wavelength is |T A -T B The difference in transmittance between the first glass matrix and the second glass matrix for light with wavelengths greater than that for fluorescence. A -L B |, and T A >T BIn the wavelength conversion components of Examples 1 to 3, phosphors can be efficiently excited even when UV light is used as excitation light, and UV light leakage can be suppressed to prevent aging of peripheral equipment and its effects on the human body.

[0132] Symbol Explanation

[0133] 1: Wavelength conversion component

[0134] 2: First layer

[0135] 2a: First Main Face

[0136] 2b: Second Main Page

[0137] 3: Second layer

[0138] 4: First glass matrix

[0139] 5: Fluorescent particles

[0140] 6: Second glass matrix

[0141] 7: Light source

[0142] 11: Light-emitting device

[0143] 12: Light guide plate

Claims

1. A wavelength conversion component for converting the wavelength of excitation light emitted from a light source, characterized in that it comprises: A first layer consisting of a first glass matrix and phosphor particles dispersed in the first glass matrix; and A second layer, disposed above the first layer and composed of a second glass matrix, The first layer is disposed on the light source side. The transmittance T of the excitation wavelength light through the first glass matrix A The transmittance T of the second glass matrix B The difference | T A -T B The transmittance L of light with wavelengths greater than fluorescence through the first glass matrix A Transmittance L of the second glass matrix B The difference | L A -L B |, and T A >T B , The difference between the light transmittance difference of the excitation wavelength and the light transmittance difference of the fluorescence wavelength |T A -T B |-|L A -L B | It is over 20%.

2. A wavelength conversion component for converting the wavelength of excitation light emitted from a light source, characterized in that it comprises: A first layer consisting of a first glass matrix and phosphor particles dispersed in the first glass matrix; and A second layer, disposed above the first layer and composed of a second glass matrix, The first layer is disposed on the light source side. The transmittance T of the excitation wavelength light through the first glass matrix A The transmittance T of the second glass matrix B The difference | T A -T B The transmittance L of light with wavelengths greater than fluorescence through the first glass matrix A Transmittance L of the second glass matrix B The difference | L A -L B |, and T A >T B , The transmittance T of the first glass matrix to light of the excitation wavelength A The transmittance T of the second glass matrix to the excitation wavelength is above 20%. B It is below 65%.

3. The wavelength conversion component as described in claim 1 or 2, characterized in that: The transmittance L of the first glass matrix to fluorescence wavelengths A The transmittance L of the second glass matrix to fluorescence wavelengths is above 50%. B It is over 50%.

4. The wavelength conversion component as described in claim 1 or 2, characterized in that: The second layer does not actually contain fluorescent particles.

5. The wavelength conversion component as described in claim 1 or 2, characterized in that: The thickness of the second layer is greater than the thickness of the first layer.

6. The wavelength conversion component as described in claim 1 or 2, characterized in that: The thickness ratio of the second layer to the first layer (second layer / first layer) is greater than 1 and less than 30.

7. The wavelength conversion component as described in claim 1 or 2, characterized in that: The excitation light is UV light.

8. The wavelength conversion component as described in claim 1 or 2, characterized in that: The fluorescence is visible light.

9. A light-emitting device, characterized in that... include: A light source that emits excitation light; and The wavelength conversion component according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Light-emitting diode

    JP2000208815A

  • Phosphor for methane gas sensor, light source for methane gas sensor and methane gas sensor

    JP2013170205A

  • Silica glass member for wavelength conversion, and production method therefor

    CN104903266A